Clinical Study of 5 Cases of Colon Diverticulitis with Colovesical Fistula Treated Laparoscopically - Nakasima, Masayuki; Yokomizo, Hiroshi; Kimura, Yu; Yamane, Takaaki; Tanaka, Eiji; Hirata, Toshihiko; Yamada, Kenji; Hayashi, Kohji (The Japanese Journal of Gastroenterological Surgery, 2011)
We report 5 cases of colovesical fistula from diverticulitis treated in laparoscopic surgery. All subjects were men of a mean age of 60.0 years and chiefly reported pneumaturia and cloudy urine. Urinary bladder air in computed tomography (CT) is useful in a definitive diagnosis, but barium enema and colonoscopy are not. All subjects underwent laparoscopic fistula separation and sigmoidectomy. No additional urinary bladder procedure was required. A covering ileostomy was added in one case. Average operating time was 280 minutes (4.67 hours), intraoperative blood loss was 43g, and urinary drainage took 7 days and postoperative hospital stay 10-11 days, except in 1 case. No mortality was seen, although 1 case of anastomotic colon leakage occurred. No malignancy was seen at the fistula pathologically. Laparoscopic surgery for colovesical fistula from diverticulitis not requiring lymph node dissection is feasible, less invasive, and more beneficial to subjects than other approaches.